Application of Bioorganic Fertilizer on Panax notoginseng Improves Plant Growth by Altering the Rhizosphere Microbiome Structure and Metabolism - Rui Shi; Shu Wang; Bingjie Xiong; Haiyan Gu; Huiling Wang; Chao Ji; Weijia Jia; Abraham Rami Horowitz; Wenjie Zhen; Jiftah Ben Asher; Xiahong He (Microorganisms, 2022)
Bioorganic fertilizers can alleviate (a) biotic stresses and sustainably increase crop yields. The effect of bioorganic fertilizers on the rhizosphere bacterial community of Panax notoginseng and soil metabolism remains unknown. Here, we tracked the changes in the soil physicochemical properties, bacterial microbiota responses, and soil metabolic functions after the addition of a bioorganic fertilizer in a P. notoginseng field. The application of a bioorganic fertilizer reduced the soil acidification, improved the organic matter, and increased the contents of the total/available soil nutrients. Soil amendment with a bioorganic fertilizer significantly affected the structure of the rhizosphere bacterial community, leading to the enrichment of specific bacterial consortia such as Rhodanobacter, Arthrobacter, Sphingomonas, Devosia, Pseudolabrys, Luteimonas, Lysobacter, Nitrosospira, and Nakamurella. Previously, many of these genera have been associated with nutrient cycling, plant productivity, and disease suppression. Metabolome analysis further highlighted that the bioorganic fertilizer treatment significantly reduced phenolic acids and flavonoids and enhanced organic acids, saccharides and alcohols, and amino acids. This result indicates a high survival of bacterial microbiota in the rhizosphere and an availability of nutrients for P. notoginseng growth. This work showed that the application of bioorganic fertilizers significantly improves soil health status, alters soil metabolic functions, and stimulates a specific subset of rhizosphere microbiota for nutrient cycling and disease protection in P. notoginseng.